Gender selection dilemma in FMCG advertising: Insights from eye-tracking research - Minanshu Sinha; Madhvendra Misra; Saurabh Mishra (Journal of Eye Movement Research)
Selecting the gender of a celebrity for fast-moving consumer goods (FMCG) advertising presents a strategic challenge. Previous research has predominantly concentrated on comparing celebrity spokespersons with non-celebrities, frequently neglecting the intricate distinctions in the effectiveness of male versus female endorsers. This study addresses this research gap by employing both traditional and neuromarketing methodologies. By integrating eye-tracking technology via RealEye and questionnaire-based surveys, the results indicate that female celebrities are more effective in capturing visual attention, whereas male celebrities are more effective in enhancing perceived trustworthiness. These findings are pivotal for both academic research and commercial strategy, as they elucidate the optimal selection of celebrity gender for maximizing FMCG advertising efficacy.